An Institutionalist Approach to Finance and an Illustrative Application to Investment Banking in the United States (1981-2008) - Cristian, Oana; García Fernández-Muro, Clara (Revista de Economía Mundial, 2020)
The 2008 US crisis revived contributions of Post-Keynesian Institutionalism (PKI) and particularly those of Hyman Minsky. As is known, his theories connected finance with macroeconomic dynamics from an institutional perspective. However, many of these Minskyan revisions focused on the Financial Instability Hypothesis (FIH) in terms of over indebtedness and fragility of balance sheets, without explicitly accounting for the relationship between finance, macroeconomic dynamics, and the institutional environment. This paper intends to deepen this threefold connection from a theoretical-methodological perspective; as well as to illustrate how the proposed framework can be applied (in this paper, to the study of investment banking in the United States in 1980-2008).